Uncanny women and Angolan unhomeliness - Rothwell, P (Brill Academic Publishers, 2024)
Women writers have contested the monolithic version of Angolan nationhood propagated by the MPLA during the struggle for independence and its aftermath. Often haunted by an instrumentalized form of “motherness”, the version of Angola fashioned by the New Man left little space for women’s agency or the recognition of their creative autonomy. This article’s central premise is that a range of women writers (exemplified by Ana Paula Tavares, Rosária da Silva, Margarida Paredes, and Chó do Guri) have contested the gendered limitations placed on them by deploying techniques grounded in the uncanny, most notably “foreignness”, “unhomeliness” and new takes on old narratives, in the process, wresting control of Mother from the New Man. The article discusses the deployment of Mother in nationalist discourse, and the extent to which this was inflected in colonial-era gender-saturated matrices. Less gender-coded research on motherhood is juxtaposed with Agostinho Neto’s “mãe” to argue that nationalist poets and authors, unwittingly or otherwise, pushed a metaphor of Mother articulated from within a colonial epistemological framework. The article suggests that the failure of the MPLA revolution should be judged as much in terms of the movement’s proclivity towards normalizing gender binaries as its inability to realize political utopia. Against a backdrop of “patriotic motherhood” that reduced women to carers, Ana Paula Tavares’s challenges to the prudish sensitivities of the New Man were expanded linguistically into the terrain of uncanny “foreignness” by Rosária da Silva. For her part, Margarida Paredes’s rewriting of the Freudian primal scene foregrounds the colonial mother as an Angolan inheritance. For Chó do Guri, the interpellation of mother replicates Neto’s strategy of calling a maternal object into being, but in an uncanny way that uses mother to tell the fraught history and present of a daughter rather than alloying her to the future of a nation.